Import Constraints and Development: Causes of the Recent Decline of Brazilian Economic Growth: A Comment - Bergsman, Joel; Morley, Samuel A. (The Review of Economics and Statistics, 1969)
Joel Bergsman, Samuel A. Morley, Import Constraints and Development: Causes of the Recent Decline of Brazilian Economic Growth: A Comment, The Review of Economics and Statistics, Vol. 51, No. 1 (Feb., 1969), pp. 101-102